Chemical Quality of Landrace Cross Meats Traditionally Used in Different Times - N. M. A., Armini; Sriyani, N. L. P.; Putri, T. I. (Jurnal Peternakan Tropika, 2019)
This study aims to determine the chemical quality of pork that has through the waking process traditionally. This study used landrace pork on commercial pieces of Loin in the Longgisimus dorsi muscle. Withering is carried out in open spaces with room temperature 28 0 C-29 0 C. The design used was a Completely Randomized Design (CRD) with four treatments and four replications, such as fresh meat that was not aging (P0), meat aging during 8 hours (P1), meat aging during 16 hours (P2), and meat aging during 24 hours (P3). The variables that observed are water content, protein content, fat content and ash content. The analysis data is using variance (ANOVA) and Duncan distance test. The proximate analysis of landrace pork meat which has traditionally undergone a process of withering at room temperature based on fresh ingredients shows that a significant decrease in moisture content, protein content and ash but in meat fat levels has increased although not significant. The conclusion of this study is the traditional length of time at room temperature decreases water content, protein content and ash content of landrace pork, while fat content did not increased different enhancement.   Keywords: tradisional withering, pork, chemical quality